Ammonia and chromate interaction explains unresolved Hyalella azteca mortality in Flanders' sediment bioassays. (May 2021) - Nolte, Tom M.; Vink, Jos P.M.; De Cooman, Ward; van Zelm, Rosalie; Elst, Raf; Ryken, Els; Hendriks, A. Jan
Abstract: Agricultural, industrial and household chemicals are emitted in large rivers along populated areas, transported by water and deposited in sediments, posing (eco)toxicological risks. Sediments have received less attention than surface waters, likely because of the intrinsic complexity of interactions between sediment constituents complicating correct framing of exposures. Sadly, thorough assessment of the in situ behavior of sediment constituents in bioassays is often not practical. Alternatively, we related physicochemical properties of sediments from field testing to results from bioassays. The case study covers Flemish sediment (incl. Scheldt and Meuse) and mortality of Hyalella azteca, a sensitive bio-indicator. Though variable across Flanders' main water bodies, heavy metals and ammoniacal nitrogen dominate the observed toxicity according to toxic unit (TU) assessments. Depending on the water body we explain between 50 and 90% of the variance in the observed H. azteca mortality, substantially more than previous ecotoxicity studies. We attribute the remaining variance to potential incoherently documented biophysicochemical sediment properties and concentrations of non-target biocides, testing conditions/set-ups and/or species variabilities. We discuss the relative influence of heavy metals/metaloxides, nitrogen (e.g. fertilizer), polycyclic aromatics and organochlorides. We highlight both direct and indirect mortality mechanisms. We note potential synergetic mixture effects between ammoniacal nitrogen and chromium. Such synergy may be phenomenological of 'standard' aerobic bioassays, and prove a complementary method alongside the 'acid-volatile sulfide test' to more effectively link concentration to toxicity. Future study ought to include variation in biophysicochemical properties between sampling locations and batch bioassays. Our approach enables water managers to interpret their monitoring data by converting sediment concentrations to H. azteca mortality and prioritize substances that contribute most. Highlights: Characterization of ecotoxicity in bioassays on Flemish sediments via toxic units. We can now explain for 50–90% of Hyalella azteca mortality due to pollution. The toxicity of chromium and ammonia dominate, but differ from single-substance aerobic tests. Differences relate to a cascade of biophysicochemical interactions affecting speciation and transformation. Differences help bridging between the field and bioassays to enable more reliable risk assessment.